1957
DOI: 10.1172/jci103546
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Nucleosides On the Resistance of Normal Human Erythrocytes to Osmotic lysis12

Abstract: The investigations reported in this paper proceeded on the hypothesis that maintenance of the structural integrity of the human erythrocyte is dependent on continued production and utilization of energy by the cell. In an attempt to test this hypothesis the susceptibility of fresh human erythrocytes to osmotic lysis was studied in terms of the influence of various compounds that might serve as substrates for energy yielding reactions within the erythrocyte. Particular attention was paid to glucose (3) and puri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
4
0

Year Published

1958
1958
1973
1973

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 20 publications
(16 reference statements)
1
4
0
Order By: Relevance
“…The finding that inosine enhances the osmotic resistance of rabbit erythrocytes is similar to that previously reported for human erythrocytes (13).…”
Section: Methodssupporting
confidence: 90%
See 2 more Smart Citations
“…The finding that inosine enhances the osmotic resistance of rabbit erythrocytes is similar to that previously reported for human erythrocytes (13).…”
Section: Methodssupporting
confidence: 90%
“…These effects include enhanced resistance to osmotic lysis (13,18), increased organic phosphate esters within the cells (18), restoration of intracellular potassium (18,19) and sodium concentrations (20), and perhaps slight prolongation of viability of in vitro stored erythrocytes (18,21,22). The decline in the effect of inosine on the osmotic resistance of rabbit erythrocytes which have aged normally in vivo may indicate either a concomitant decline in the ability of the erythrocyte to metabolize the purine riboside or in its ability to utilize the energy produced by the metabolism of inosine as the result of irreversible changes which have occurred in the cell.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This aspect of the "storage lesion" has been studied extensively by Rapoportlz and was used to estimate the extent of erythrocyte deterioration during storage. [3][4][5][6][7][8][9] A rapid micromethod for determination of osmotic fragility by gradual decrease of ionic strength of the medium surrounding the erythrocytes has been described recently.' An instrument ("fragiligraph") for automatic recording of the cumulative and/or the derivative curve was constructed.2 'This method requires less than 0.1 ml.…”
mentioning
confidence: 99%
“…Previous studies in this and other laboratories have demonstrated that normal human erythrocytes can metabolize the pentose moiety of certain purine nucleosides to lactic acid in vitro (9,10). This metabolic activity is associated with enhanced resistance to osmotic stress (11,12), increased organic phosphate esters (11), retention of potassium (11) and extrusion of sodium (13), maintenance of reduced glutathione (14,15) and some prolongation of viability of erythrocytes stored in vitro (11,16,17).…”
mentioning
confidence: 99%